Downregulation of PIM1 regulates glycolysis and suppresses tumor progression in gallbladder cancer - Xue C (Cancer Management and Research, 2018)
Chen Xue,1,2,* Yuting He,1,2,* Qiuyue Hu,1,2 Yan Yu,1,2 Xiaolong Chen,1,2 Jianan Chen,1,2 Fang Ren,2 Juan Li,1,2 Zhigang Ren,1,2 Guangying Cui,1,2 Ranran Sun1–3 1Precision Medicine Center, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, China; 2Key Laboratory of Clinical Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, China; 3National Engineering Laboratory for Internet Medical Systems and Applications, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, China *These authors contributed equally to this work Background: PIM1, a serine/threonine kinase, plays an essential role in tumorigenesis of multiple types of tumors. However, the expression pattern and functions of PIM1 in gallbladder cancer (GBC) remain largely unknown. Materials and methods: Immunohistochemistry, quantitative real-time PCR, and western blot analysis were performed to measure the expression of PIM1. Tissue microarray analysis was used to confirm the relationship between PIM1 expression and clinical outcomes of GBC patients. Finally, in vivo and in vitro functional studies were performed to detect the inhibition of PIM1 by RNAi or specific inhibitor in GBC cells. Results: We observed that PIM1 was dramatically overexpressed in GBC tissues, and its expression levels were positively related with clinical malignancies and a poor prognosis. Inhibition of PIM1 via RNAi or enzyme-specific inhibitor could suppress GBC cell proliferation, migration, and invasion both in vitro and vivo. Additionally, flow cytometry assays and cell cycle assays indicated that PIM1 inhibition promoted cell apoptosis and induced cell cycle arrest. Remarkably, inhibition of PIM1 could drive a metabolic shift from aerobic glycolysis to oxidative phosphorylation. We found that inhibition of PIM1 mechanistically reduced glucose consumption by regulating key molecules in aerobic glycolysis. Conclusion: PIM1 may serve as an oncogene in GBC and be involved in the regulation of glycolysis. PIM1 is a promising therapeutic target for the treatment of human GBC. Keywords: PIM1, gallbladder cancer, aerobic glycolysis, tumor progression